Quasi context sensitive graph grammars as a formal model of FE mesh generation - Flasiński, Mariusz; Schaefer, Robert (Computer Assisted Methods in Engineering and Science, 2023)
Mathematical linguistics models that can be useful for controlling FE mesh generation are presented in the paper. The problems concerning an application of formal grammars for this purpose are outlined. Advantages and drawbacks related to the use of various types of Lindenmayer string/graph systems applied recently for FE mesh generation are discussed. An efficient (parsable) class of ETPL(k) graph grammars is proposed as a formal tool in this research area.